(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Damage caused by the white snail Cernuella virgata (Da Costa, 1778) was for the first time observed in vegetable crops in Serbia during the summers of 2011 and 2012. In this country, serious damage to vegetable crops is usually caused by slugs, while snails do not normally cause any significant harm. Typical xerophilic snail species in the genera Cernuella, Xerolenta and Theba cause damage even more rarely since they are limited to wild flora in uncultivated and ruderal areas, and local outbreaks occur seldom and only in forage leguminous crops. The species C. virgata was for the first time found to cause damage to a number of vegetable crops during long periods of extremely warm and dry weather, including total devastation of a green onion crop.